2018
DOI: 10.1002/jso.25026
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus open pancreatic enucleation. Systematic review and meta‐analysis of surgical outcomes

Abstract: Parenchymal sparing procedures are gaining interest in pancreatic surgery and recent studies have reported that minimally invasive pancreatic enucleation may be associated with enhanced outcomes when compared with traditional surgery. By meta-analyzing the available data from the literature, minimally invasive surgery is not at higher risk of pancreatic fistula and offers a number of advantages over conventional surgery for pancreatic enucleation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 72 publications
0
8
1
1
Order By: Relevance
“…These report shorter operative time, less blood loss, and reduced hospital stay for the former [56][57][58][59]. A systematic review from Guerra et al confirmed these findings, while the rates of clinically relevant POPF and major complications were similar [60]. Although initially considered for left-sided pancreatic lesions only, MIPE has also been successfully applied for tumors in the pancreatic head [59,61].…”
Section: Other Minimally Invasive Proceduresmentioning
confidence: 88%
“…These report shorter operative time, less blood loss, and reduced hospital stay for the former [56][57][58][59]. A systematic review from Guerra et al confirmed these findings, while the rates of clinically relevant POPF and major complications were similar [60]. Although initially considered for left-sided pancreatic lesions only, MIPE has also been successfully applied for tumors in the pancreatic head [59,61].…”
Section: Other Minimally Invasive Proceduresmentioning
confidence: 88%
“…Over the past decade, there has been a rapid increase in the adoption of laparoscopic and robotic pancreatic surgery with numerous studies demonstrating its superiority especially in terms of shorter hospital stay and quicker convalescence over its traditional open counterpart 6789. Presently, both laparoscopic and robotic approaches have been reported for the various types of pancreatectomies including DP, PD, central pancreatectomies and enucleations 56714. More recently, 2 single-center randomized controlled trials have confirmed the superior short-term outcomes of laparoscopic PD over its open counterpart 910…”
Section: Discussionmentioning
confidence: 99%
“…an overall 31% risk of POPF after surgery which was equivalent (Z = 0.75, p = 0.45) between the open (33%) and MIS (28%) cohorts. 8 Similarly, all of these studies, including Chua et al, 19 demonstrate a significant one day reduction in length of stay after MIS enucleation. Despite similar rates of POPF between the open and MIS cohorts, prior reviews have indicated potentially significant benefits of MIS enucleation in terms of operating time and major morbidity.…”
Section: Meta-analysis Of 413 Open and Mis Enucleations Demonstratedmentioning
confidence: 90%
“…6,7 Postoperative pancreatic fistula is the most commonly reported complication but rarely causes severe morbidity. 8,9 Given strictly defined patient selection criteria for enucleation, surgical decisions regarding an open and minimally-invasive approach are less prone to confounding by indication during non-randomized comparisons, unlike distal pancreatectomy and radical pancreatoduodenectomy. A recent meta-analysis of minimally-invasive enucleation demonstrated reduced hospital stay and overall morbidity compared to open without an increase in postoperative pancreatic fistula 8 but was limited to single institution cohorts without standardized variables, evaluation for publication bias, or investigation of patient selection criteria.…”
Section: Introductionmentioning
confidence: 99%